Grafting to increase high tunnel tomato productivity in the central United States - Meyer, Lani (Kansas State University, 2016)
As populations of cities continue to increases, communities in the United States are implementing urban food systems including locally-cultivated produce. Urban and peri-urban farmers apply intensive production systems, including high tunnels, to better utilize limited space. Grafting tomato with vigorous rootstocks provides the potential for higher yields. Our first objective was to identify tomato rootstocks that improve productivity in high tunnel environments with no soilborne diseases in the Central U.S. Eight replicated high tunnel trials were conducted at four sites in northeastern Kansas in 2013 and 2014. We selected 'BHN 589' scion for all sites and evaluated seven rootstocks. Grafting with ‘Maxifort’, ‘Multifort’, ‘Arnold’, ‘DRO 131’, and ‘Colosus’ rootstocks resulted in significant increases in total fruit yield, which ranged from 40% to 73% when compared to nongrafted plants (P<0.05). No significant increases in yield were observed for ‘RT-1028’ and ‘RST-04-106’ rootstocks. Our results suggested that tomato growers that utilize high tunnels should be strategic when selecting rootstocks. Our second objective was to develop simple propagation techniques that yield high quality grafted transplants for small-batch propagators. Formation of adventitious roots (AR) from the scion can result in poor quality plants and loss of rootstock function/benefit. Greenhouse studies were designed to investigate how leaf removal (LR) affects AR formation and plant growth post-grafting. We applied three treatments, 0% LR, 50% LR, and 90% LR, to the ‘BHN 589’ scion and then grafted them onto ‘Maxifort’ rootstock. The experiment included 4 replicated blocks and was conducted in three different healing chambers. Our results indicate that both 50% and 90% LR significantly decreased AR formation in the low humidity chamber, but only 90% LR reduced AR formation in the chambers with high humidity (P<0.05). We measured plant growth 24 to 52 days post-grafting to understand how leaf removal affects transplant quality, growth, and development. Plants with 90% LR had significant growth reduction at day 24 but at day 52, only had reduced stem diameter and height compared to 0% LR. Total flower count was the same for all treatments. Leaf removal during grafting may be a viable method for propagating high quality, grafted transplants.
Keywords: Tomato production; Grafting; High tunnel; Urban agriculture